"Poor little Queensland": Resisting Six O'clock Closing in the "Hot‐bed of Disloyalty", 1915‐1918. (5th October 2018) - Cryle, Mark
Abstract : The First World War precipitated an upsurge in temperance campaigning. Inspired by a dominant discourse of sacrifice and self‐denial, most state legislatures introduced reduced trading hours for hotels. Queensland was the exception. Six o'clock closing was resisted in the northern state despite a vigorous and rancorous campaign for its introduction. This paper maps the contours of the debates around early closing and temperance in Queensland. Like so many other tensions induced by the war, the campaign both generated and was evidence for deep divisions in Queensland society around class, politics and religion.